The Gene Expression of Human Endothelial Cells Is Modulated by Subendothelial Extracellular Matrix Proteins: Short-Term Response to Laminar Shear Stress - Chlupac, Jaroslav (Mary Ann Liebert, Inc., 2014)
Vascular surgery for atherosclerosis is confronted by the lack of a suitable bypass material. Tissue engineering strives to produce bio-artificial conduits to provide resistance to thrombosis. The objectives of our study were to culture endothelial cells (EC) on composite assemblies of extracellular matrix proteins, and to evaluate the cellular phenotype under flow. Cell-adhesive assemblies were fabricated on glass slides as combinations of collagen (Co), laminin (LM), and fibronectin (FN), resulting in three samples: Co, Co/LM, and Co/FN. Surface topography, roughness, and wettability were determined. Human saphenous vein EC were harvested from cardiac patients, cultured on the assemblies and submitted to laminar shear stress (SS) of 12 dyn/cm(2) for 40, 80, and 120 min. Cell retention was assessed and qRT-PCR of adhesion genes (VE-cadherin, vinculin, KDR, CD-31 or PECAM-1, β(1)-integrins) and metabolic genes (t-PA, NF-κB, eNOS and MMP-1) was performed. Quantitative immunofluorescence of VE cadherin, vinculin, KDR, and vonWillebrand factor was performed after 2 and 6 h of flow. Static samples were excluded from shearing. The cells reached confluence with similar growth curves. The cells on Co/LM and Co/FN were resistant to flow up to 120 min but minor desquamation occurred on Co corresponding with temporary downregulation of VE cadherin and vinculin-mRNA and decreased fluorescence of vinculin. The cells seeded on Co/LM initially more upregulated vinculin-mRNA and also the inflammatory factor NF-κB, and the cells plated on Co/FN changed the expression profile minimally in comparison with the static control. Fluorescence of VE cadherin and vonWillebrand factor was enhanced on Co/FN. The cells cultured on Co/LM and Co/FN increased the vinculin fluorescence and expressed more VE cadherin and KDR-mRNA than the cells on Co. The cells plated on Co/FN upregulated the mRNA of VE cadherin, CD-31, and MMP 1 to a greater extent than the cells on Co/LM and they enhanced the fluorescence of VE cadherin, KDR, and vonWillebrand factor. Some of these changes sustained up to 6 h of flow, as confirmed by immunofluorescence. Combined matrices Co/LM and Co/FN seem to be more suitable for EC seeding and retention under flow. Moreover, Co/FN matrix promoted slightly more favorable cellular phenotype than Co/LM under SS of 2–6 h.